Genetic association between gene expression profiles in oligodendrocyte precursor cells and psychiatric disorders - Kondo, Reon; Kimura, Hiroki; Ikeda, Masashi (Frontiers in Psychiatry, 2025)
BackgroundAlthough neuronal dysfunction has been the focus of many studies on psychiatric disorders, accumulating evidence suggests that white matter abnormalities and oligodendrocyte lineage cells, including oligodendrocyte precursor cells (OPCs), play an important role. Beyond their established contribution to myelination, synaptic genes in OPCs form connections to neurons and influence neuronal circuits and plasticity, thereby potentially contributing to psychiatric pathology.MethodsWe analyzed publicly available single–nucleus RNA sequencing (snRNA–seq) data from white matter cells of healthy donors with SCZ genome–wide association study (GWAS) summary statistics. We assessed cell–type–specific enrichment of SCZ–associated genetic variants and performed weighted gene co–expression network analysis (WGCNA) to identify disease–related gene modules in implicated cell types.ResultsOPCs exhibited significant enrichment of SCZ–associated genetic risk variants and showed pronounced specificity in gene expression patterns. Through WGCNA, we identified a distinct co–expression module in OPCs that was enriched for synaptic genes associated with SCZ.ConclusionThe present results highlight the previously underappreciated role of OPCs in psychiatric disorders, suggesting that OPC–involved synaptic interactions may contribute to the pathophysiology of SCZ. This work underscores the importance of considering OPCs as active players in neural network dysfunction, with potential implications for future therapeutic strategies.